PENENTU UPAH REGIONAL: TENAGA KERJA TERDIDIK (SKILLED LABOR) DAN TIDAK TERDIDIK (UNSKILLED LABOR) DI INDONESIA - Nihayah, Dyah Maya; Kusumantoro, K (JEJAK: Jurnal Ekonomi dan Kebijakan, 2010)
The wage have impacts on poverty, living standards and the incentive to improve labor productivity (human capital), in particular, for economic growth. Regional decentralization has implications, which, they must be developed regional endowment to get the efficiency in production process. So it is interesting to examine the importance of regional characteristics in the observed variability of regional wage in Indonesia. Based on this idea, the objective of this study is to examine the contribution of regional characteristics to the regional wage differential in Indonesia. Data supplied by the Indonesian Central Bureau of Statistics during 2003 – 2007. In this study used 3 model; Ordinary Least Square (OLS), Co-Varian Model and Generalized Least Squared (GLS). Then, the most effective model based on the smallest standard error was chosen to estimate regional characteristics in the observed variability of regional wage inIndonesia. The result showed that the regional characteristics, particularly skilled or unskilled labor, play an important role in determining the wage differentials in region. The empirical evidence presented that regional economic growth and the existing of high skilled labor in labor market have positive impact toward spatial wage. Then, skilled labor and unskilled will give negative influence in regional wage. The points out is laboring existence with level education or skilled level, despite not works or was working have influence toward the regional wage. Therefore, labor's policy is expected gets focused on given specialization corresponds to that region characteristics.